2016
DOI: 10.1002/2016gc006545
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic epeirogeny of the Indian peninsula

Abstract: Peninsular India is a cratonic region with asymmetric relief manifest by eastward tilting from the 1.5 km high Western Ghats escarpment toward the floodplains of eastward‐draining rivers. Oceanic residual depth measurements on either side of India show that this west‐east asymmetry is broader scale, occurring over distances of > 2000 km. Admittance analysis of free‐air gravity and topography shows that the elastic thickness is 10 ± 3 km, suggesting that regional uplift is not solely caused by flexural loading.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 213 publications
(395 reference statements)
4
42
0
Order By: Relevance
“…On a regional perspective, the sprawl and number of sub‐basins found to be tectonically active according to the Smf values are on a decreasing trend from south toward north and provide affirmative evidence to the previous inference of diminutive tectonism from S–N as a result of reducing ridge push and uplift. These inferences also concur with the report of emergence of WGE that proceeded from south–north since Early Cenozoic and continual tilt toward east, intensively since 25 Ma (Richards et al ().…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On a regional perspective, the sprawl and number of sub‐basins found to be tectonically active according to the Smf values are on a decreasing trend from south toward north and provide affirmative evidence to the previous inference of diminutive tectonism from S–N as a result of reducing ridge push and uplift. These inferences also concur with the report of emergence of WGE that proceeded from south–north since Early Cenozoic and continual tilt toward east, intensively since 25 Ma (Richards et al ().…”
Section: Discussionsupporting
confidence: 91%
“…Although the reversal of drainage flow directions was initiated by the evolution of WGE (Fainstein et al, ) during early Cenozoic, significant denudation due to tectonics (to provide slope and continued emergence of provenance) with the active support by climate (to provide conducive milieu for weathering and pedogenesis) caused extensive basinfills during Miocene–Pliocene as indicated by extensive delta development all along the eastern continental margin of India (Singh & Swamy, ). Richards et al () reported significant tectonic tilt toward east since 25 Ma that continue until today. Ramkumar et al () stated that during the Neogene, inherited Gondwana structures were reactivated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum misfit between observed and calculated river profiles is obtained for a value of m 0:45. The locus of this minimum is not strongly dependent on the degree of spatial or temporal smoothing that is applied, contra Richards et al (2016). We aim to find values of the two damping parameters that yield the smoothest possible model which still adequately fits the observed river profiles.…”
Section: Model Calibrationmentioning
confidence: 99%
“…Subsequently, Roberts et al [2012a] developed a non-linear optimization scheme that permits substantial inventories of river profiles to be simultaneously inverted by varying uplift rate history as a function of both time and space. This general scheme has been successfully applied to different continents and suggests that the empirical stream-power formulation provides a practical basis by which patterns of regional uplift through space and time can be assessed [Roberts et al, 2012b;Czarnota et al, 2014;Paul et al, 2014;Wilson et al, 2014;Stephenson et al, 2014;Richards et al, 2016].…”
Section: Modeling Strategymentioning
confidence: 99%